MOLECULAR CHARACTERIZATION OF GENETIC RESISTANCE TO SOYBEAN CYST NEMATODE IN SOYBEAN LINE SS97-6946 - Md. Sariful Islam (Journal of Animal and Plant Sciences, 2015)
Breeding resistant cultivars is the most efficient means to control soybean cyst nematode (SCN) but the nematode overcomes the resistance. A study was conducted to identify Quantitative Trait Loci (QTL) conferring broad-spectrum SCN resistance in SS97-6946 at University of Missouri, USA. A set of 160 F2 individuals from the cross PI 567476 X SS97-6946 was genotyped with 347 Single Sequence Repeat and evaluated against four races of SCN bioassay. Three markers mapped on linkage groups (LG) A2, E, and G, accounting for 33.8% of the total phenotypic variance for resistance to HG type 2.5.7. One resistant QTL, detected on LG A1 accounted for 18.8% of the total phenotypic variance of HG type 1.2.5.7. Three resistance QTL detected on LGs A2, G, and M that shared 24.9% of the total phenotypic variance HG type 0. Three QTL on LG G alone and another four on LGs A1, B2, M, and O were linked with SCN resistance to HG type 1.2.7 that accounted for 70.8% of the total phenotypic variance. Resistant QTL on LGs A1, M and O in SS97-6946, appear to be unique for SCN HG types 1.2.5.7, 0, and 1.2.7 that can potentially be used in marker assisted selection.
Keywords: Glycine max; Heterodera glycines; HG type; linkage group; quantitative trait loci